Legal Protection Strategies for Child Adoption Without a Court Order: A Comparative Study of Indonesia, USA and Malaysia - Imtina, Salma Salsabila; Aprilianda, Nurini; Widyanti, Yeni Eka (Institut Agama Islam Negeri Curup, 2024)
This study conducts a comprehensive examination of the frameworks designed to protect the rights of children adopted informally, without judicial oversight. It focuses specifically on the mechanisms that support their legal recognition and inheritance rights within adoptive families. Employing a normative research approach, the paper investigates the legal challenges arising from the lack of clear statutory provisions for these children's protection. Primary legal sources including the Child Protection Law, Law Number 25 of 2014, which revises Law Number 23 of 2002, and Government Regulation Number 54 of 2007 concerning Child Adoption procedures are analyzed. Further insights are derived from secondary sources such as the Minister of Social Affairs Regulation Number 3 of 2018, which describes the protocols for monitoring and reporting on the child adoption process. The study identifies three potential strategies to safeguard the interests of informally adopted children: formalization of adoption through notarial deeds, securing inheritance rights through wills, and maximizing protection under national child welfare laws. These measures offer vital safeguards for these children, particularly in securing inheritance claims and preventing disputes. The findings highlight the need for explicit legal frameworks to ensure the welfare and rights of children adopted outside formal judicial systems.